Islamization of Knowledge Base Education in Islamic Boarding School to Face the Challenges of Western Civilization in 21st Century - Muhammad Ghifari (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2021)
Islamic education faces serious challenges in modern era. One of these challenges was born as a result of massive Western secularism occurring in a number of countries where the majority of the population is Muslim. In Indonesia, for example, the education system in modern Islamic boarding school has been affected by the secularization process. Although there is no dichotomy between science and religion, there are still indications of secularism which only focuses on the implementation of general science learning. This article offers a knowledge-based Islamic boarding school education model as an alternative solution to minimize the occurrence of Islamic boarding school education secularization projects in Indonesia. By using a philosophical approach, this study wants to show that the Islamization of knowledge will be able to transform the orientation of the vision of educational institutions, and change the way students, kiai, ustadz and teachers think about general sciences. This paper concludes that the paradigm of learning general science in Islamic boarding schools should be oriented to two balances, namely aimed at meeting human needs without forgetting the divine aspect. Thus, the goals of Islamic education can be achieved better.